2017
DOI: 10.5530/jyp.2017.9.64
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic, Antihyperlipidemic, Antioxidant Property of Cordia obliqua on Streptozotocin Induced Diabetic Rats

Abstract: Objective:The main objective is to investigate the antidiabetic, antihyperlipidemic and antioxidant activity of methanolic extract of Cordia obliqua (MECO) in streptozotocin-induced diabetic rats. Methods: Acute toxicity study of MECO was carried out in rat to determine its dose for further study. Oral glucose tolerance test was performed to evaluate MECO on elevated blood glucose levels. Diabetes was induced in rats by administration of streptozotocin (STZ) (45 mg/kg) and it was confirmed 3 days after inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In diabetic rats, a marked increase in Serum TG, LDL and VLDL levels and a decrease in HDL level were observed. These observations could be supported with reports documented earlier [63][64][65] . In this study, sample extracts have shown lowering of TG, TCH, LDL and VLDL levels and increase in HDL level compared to the control group.…”
Section: Normal Diabetic Control Glibenclamidesupporting
confidence: 93%
“…In diabetic rats, a marked increase in Serum TG, LDL and VLDL levels and a decrease in HDL level were observed. These observations could be supported with reports documented earlier [63][64][65] . In this study, sample extracts have shown lowering of TG, TCH, LDL and VLDL levels and increase in HDL level compared to the control group.…”
Section: Normal Diabetic Control Glibenclamidesupporting
confidence: 93%
“…A phase of hypoglycemia occurs due to four-fold increase in serum insulin level, and this phase is followed by persistence hyperglycemia. 12 In recent times a new animal model of Type 2 diabetes has been suggested by combining STZ and NAD in adult rats (160-240 gm).…”
Section: Methodsmentioning
confidence: 99%
“…obliqua Willd. plant extracts possess antihyperlipidemic and antioxidant properties with potential application as an oral anti-hypoglycemic agent in the treatment of diabetes (Table 5, Ramakrishnan et al, 2017). The leaves of C. obliqua Willd.…”
Section: Medicinal Propertiesmentioning
confidence: 99%